Pencegahan Karies Gigi pada Anak Padukuhan Nglambur Kelurahan Sidoharjo Kecamatan Samigaluh (DENSITY 2023) - Bayu Ananda Paryontri; Wustha Farani; Sartika Puspita; Indah Komala Dewi; Aisyah Salsabila (Dental Agromedis, 2023)
Dental and oral health is very important and fundamental, if it is not treated it can cause problems both locally and generally. Awareness to be able to apply a healthy lifestyle is needed in maintaining healthy teeth and mouth. Counseling and community service is one of the most important preventive efforts. Dental Emergency Social Charity (DENSITY) is a community service program organized by dental emergency (DENMER) which is a student activity unit for the Department of Dentistry (UKMJ) Faculty of Dentistry UMY. The purpose of this activity is to prevent an increase in the number of dental and oral health problems in Indonesia, especially dental caries. This activity was carried out in the Nglambur hamlet, Sidoharjo, Samigaluh District, Kulon Progo Regency, Special Region of Yogyakarta. The target of this activity is children and adults. The method of this activity is counseling and prevention of dental caries in children, namely the topical application of fluoride and fissure sealant. The results of the service showed that there was an increase in participants' knowledge about dental and oral health. Based on the pretest, an average value of 65.3 was obtained. After the counseling was carried out, there was an increase in the post- test average score for correct answers, which was 80 and there were 10 participants with all correct answers. The conclusion of the results of this community service is that there is an increase in the knowledge and skills of the service participants regarding dental and oral health.Keywords: Caries, Dental and oral health, Preventive.